Does the black industrialist programme responds to south Africa’s industrialisation challenges? - Saravanja, Dhyan (University of the Witwatersrand, Johannesburg, 2024)
This study explores the extent to which the Black Industrialist Programme (BIP) is able to fulfil its stated mandate of promoting industrialisation in South Africa. In doing so, it redirects the focus away from policy design and instead evaluates the efficacy of the programme’s mechanisms of monitoring and adjustment. Using a qualitative, inductive research approach, this study finds that the BIP’s ability to promote industrialisation is strongly compromised by the quality of its reciprocal control mechanisms. Firstly, the evaluation of firm performance against the programme’s industrial objectives either relies on check-box measures, or is outsourced entirely to private auditors. Secondly, the government is poorly capacitated to perform a rigorous monitoring function. Thirdly, the state lacks both the capacity and willingness to enforce disciplinary measures on underperforming firms. Whether the BIP evolves into a genuine instrument of industrial policy rests on addressing these shortcomings. This requires placing learning at the forefront of policy reform efforts
A research report submitted in fulfillment of the requirements for the Master of Commerce (Applied Development Economics), In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Black Industrialist Programme (BIP); BEE; SDG-8: Decent work and economic growth